Pengembangan Sistem Informasi Akademik Berbasis Website Menggunakan Laravel dengan Pendekatan Agile Development - Arlina, Esa; Jemakmun, Jemakmun (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This academic information system was developed for SMK Negeri 1 BP Bangsa Raja using the Agile Development method. Its purpose is to digitize the management of school academic data, provide teachers and students with real-time access to information, enhance transparency, and improve administrative efficiency. The system was built using Laravel as the main framework, Jetstream for authentication management, and Tailwind CSS for interface design. Development was carried out in stages and adaptively, involving teachers and students as the primary users. Testing results showed that the system is easy to use, received positive feedback, and effectively supports the school’s digital transformation. This system is considered a sustainable digital solution for academic and administrative activities.
Keywords: Laravel; Jetstream; Tailwindcss; Agile Development